IMPLEMENTASI MODEL PEMBELAJARAN JIGSAW UNTUK MENANAMKAN NILAI TANGGUNG JAWAB DAN NILAI KERJA KERAS - Chinta N.A Ismayawiaty; Abdul Hakim (Bale Aksara: Jurnal Pendidikan Sekolah Dasar, 2020)
This research is motivated by the learning model used by teachers when teaching and learning activities in character building so that there is a need for positive character planting in accordance with the national education goals set in Law No. 20 of 2003. The purpose of this research is to find out (1) Application of Jigsaw learning model. (2) Value of responsibility and value of hard work. (3) Students' perceptions of the use of Jigsaw learning models in instilling the value of responsibility and the value of hard work. The benefit of this research is that it can provide an overview of the implementation of the Jigsaw learning model to instill the value of responsibility and the value of hard work. The method used in this research is quantitative descriptive method. Data obtained from this study is to spread questionnaires and make observations. Based on the data collected and the results of the analysis of this study, the conclusions can be drawn as follows: (1) The implementation of the Jigsaw learning model is classified as good or it can be said that almost all activities have been carried out by the teacher, this can be proven by the largest observation results, 83, 33%. (2) The responsibility and hard work of students is classified as good category, with the largest acquisition, namely the value of responsibility with 25 students and the value of hard work with 24 students. (3) Students' perceptions regarding the implementation of the Jigsaw learning model to instill the value of responsibility and the value of hard work get a positive response. This can be proven by the acquisition of a questionnaire with a total of 18 items from 37 items.